Enhancing Social-Emotional Health and Wellbeing in the Early Years (E-SEE): a study protocol of a community-based randomised controlled trial with process and economic evaluations of the incredible years infant and toddler parenting programmes, delivered in a proportionate universal model. Issue 12 (19th December 2018) - Bywater, Tracey; Berry, Vashti; Blower, Sarah Louise; Cohen, Judith; Gridley, Nicole; Kiernan, Kathleen; Mandefield, Laura; Mason-Jones, Amanda; McGilloway, Sinead; McKendrick, Kirsty; Pickett, Kate; Richardson, Gerry; et al.
Abstract : Introduction: Behavioural and mental disorders have become a public health crisis and by 2020 may surpass physical illness as a major cause of disability. Early prevention is key. Two Incredible Years (IY) parent programmes that aim to enhance child well-being and development, IY Infant and IY Toddler, will be delivered and evaluated in a proportionate universal intervention model called Enhancing Social-Emotional Health and Wellbeing in the Early Years (E-SEE) Steps. The main research question is: Does E-SEE Steps enhance child social emotional well-being at 20 months when compared with services as usual? Methods and analysis: E-SEE Steps will be delivered in community settings by Early Years Children's Services and/or Public Health staff across local authorities. Parents of children aged 8 weeks or less, identified by health visitors, children's centre staff or self-referral, are eligible for participation in the trial. The randomisation allocation ratio is 5:1 (intervention to control). All intervention parents will receive an Incredible Years Infant book (universal level), and may be offered the Infant and/or Toddler group-based programme/s—based on parent depression scores on the Patient Health Questionnaire or child social emotional well-being scores on the Ages and Stages Questionnaire: Social Emotional, Second Edition (ASQ:SE-2). Control group parents will receive services as usual. A process and economic evaluation are included. The primary outcome for the study is social emotional well-being, assessed at 20 months, using the ASQ:SE-2. Intention-to-treat and per protocol analyses will be conducted. Clustering and hierarchical effects will be accounted for using linear mixed models. Ethics and dissemination: Ethical approvals have been obtained from the University of York Education Ethics Committee (ref: FC15/03, 10 August 2015) and UK NHS REC 5 (ref: 15/WA/0178, 22 May 2015. The current protocol is Version 9, 26 February 2018. The sponsor of the trial is the University of York. Dissemination of findings will be via peer-reviewed journals, conference presentations and public events. Trial registration number: ISRCTN11079129 ; Pre-results.